The Role of Motivation in Connecting Work Environment and Employee Performance: Insights from Indonesia - Maniah, Maniah; Bon, Abdul Talib; Hariadi, Andi Kahar (International Journal of Industrial Engineering, Technology & Operations Management, 2024)
Employee performance is a critical factor for the success and sustainability of any organisation, and understanding the key drivers of employee performance is crucial for researchers and practitioners. This study, conducted at the Indonesian Classification Bureau, aimed to investigate the influence of the work environment on employee performance, with employee motivation as a mediating variable. The study population comprised the entire workforce of the Indonesian Classification Bureau, with a total of 35 individuals. The Structural Equation Model, processed using Smart PLS software, was employed as the analysis tool. The results demonstrated a significant influence of social support on organizational commitment among employees of the Indonesian Classification Bureau. Also, the study found a significant influence of family-work conflict on the social support experienced by employees. Additionally, family-work conflict had a significant effect on organizational commitment. The study also revealed an effect of family-work conflict on organizational commitment, with social support functioning as a mediating variable for employees of the Indonesian Classification Bureau.